Comparison of Acute and Subacute Genitourinary and Gastrointestinal Adverse Events of Radiotherapy for Prostate Cancer Using Intensity-modulated Radiation Therapy, Three-dimensional Conformal Radiation Therapy, Permanent Implant Brachytherapy and High-dose-rate Brachytherapy. Issue 3 (May 2014) - Morimoto, Masahiro; Yoshioka, Yasuo; Konishi, Koji; Isohashi, Fumiaki; Takahashi, Yutaka; Ogata, Toshiyuki; Koizumi, Masahiko; Teshima, Teruki; Bijl, Henk P.; van der Schaaf, Arjen; Langendijk, Johannes A.; Ogawa, Kazuhiko
Aims and Background: To examine acute and subacute urinary and rectal toxicity in patients with localized prostate cancer monotherapeutically treated with the following four radiotherapeutic techniques: intensity-modulated radiation therapy, three-dimensional conformal radiation therapy, low-dose-rate permanent implant brachytherapy using I-125 seeds, and high-dose-rate brachytherapy. Methods: One hundred and fifty-six patients with localized prostate cancer were distributed as follows: 57 underwent intensity-modulated radiation therapy, 35 underwent three-dimensional conformal radiation therapy, 37 underwent I-125 implant, and 27 underwent high-dose-rate brachytherapy. The prescribed doses were 70–74 Gy/35–37 fractions, 70 Gy/35 fractions, 145 Gy, and 45.5 Gy/7 fraction/4 days for intensity-modulated radiation therapy, three-dimensional conformal radiation therapy, I-125 implant, and high-dose-rate brachytherapy, respectively. Toxicities (≤6 months) were retrospectively evaluated using the Common Terminology Criteria for Adverse Events version 4.03. Results: The frequency of grade 1 or 2 urinary toxicities using three-dimensional conformal radiation therapy (33/35, 94%) was significantly higher than that with high-doserate brachytherapy (18/27, 67%) or intensity-modulated radiation therapy (37/57, 65%) (P <0.05). The frequency of grade 1 or 2 urinary toxicities using I-125 implant was 31/37, 84%. The frequency of grade 1 or 2 gastrointestinal toxicities using three-dimensional conformal radiation therapy (17/35, 49%) was significantly higher than that using I-125 implant (4/37, 11%) or high-dose-rate brachytherapy (0/27, 0%) (P <0.05). Using intensity-modulated radiation therapy, the frequency of grade 1 or 2 gastrointestinal toxicities was 18/57 (32%), which was significantly higher than that using high-dose-rate brachytherapy (0/27, 0%) (P <0.05). Grade 3 or greater adverse events were not observed. Conclusions: Acute and subacute genitourinary toxicities were observed more frequently after three-dimensional conformal radiation therapy than after high-doserate brachytherapy or intensity-modulated radiation therapy. Acute and subacute gastrointestinal toxicities were seen more often after three-dimensional conformal radiation therapy than after brachytherapy (I-125 implant or high-dose-rate brachytherapy).